Two Decades of Community Responses Reveal a Consistent Increase in Species Occurrences in South‐Eastern Pacific Rocky Shores - Mauricio H. Oróstica; Paulina A. Arancibia; Otso Ovaskainen; Sergio A. Navarrete; Bernardo R. Broitman (Global Ecology and Biogeography, 2025)
Aim Understanding how diverse communities respond to environmental fluctuations is a central challenge in ecology. Here, we assessed how communities responded to environmental variation over the past 23 years and evaluated the extent to which these responses can be associated with taxonomic relationships, as well as biological and ecological species traits. Location Central portion of the Humboldt Upwelling Ecosystem, with 22 rocky shore survey sites spanning 8° of latitude (28° S–36° S). Time Period 2000–2023. Major Taxa Studied Intertidal zone communities. Methods We used joint species distribution models to integrate quantitative survey data, satellite sea surface temperature (SST) as a proxy for environmental conditions, taxonomic information and species biological traits along a latitudinal gradient with heterogeneous thermal conditions. Results Our proxy for environmental variation revealed weak and non‐significant SST cooling at central sites, whereas sites near 30° S showed slight warming trends. Taxonomic relationships and individual species traits were weakly associated with their collective responses to SST variability. However, we identified a consistent increase in the occurrence of both macroalgal and invertebrate species across the region. The occurrence of macroalgal species was more sensitive to SST variation than invertebrates, with responses shifting from positive at equatorward sites to increasingly negative at poleward sites. Patterns of species co‐occurrence were strongly dependent on spatial scale, particularly among invertebrates. Main Conclusions Species occurrences increased across the region, but these responses were not significantly associated with taxonomic relatedness or with easily assigned species traits. This pattern likely indicates comparatively low niche conservatism within these communities in relation to SST responses, while other structuring processes—such as species interactions—are not well captured by the traits examined. As other studies have detected slight cooling trends over the past two decades, our results suggest that the lack of community‐wide reorganisation reflects the absence of a clear environmental driver.

Potential of mesenchymal stromal/stem cells and spermatogonial stem cells for survival and colonization in bull recipient testes after allogenic transplantation - Moisés N. Segunda; Jahaira Cortez; Carlos Díaz; Richard Arancibia; Cristian G. Torres; Víctor H. Parraguez; Mónica De los Reyes; Oscar A. Peralta (Theriogenology, 2024)

Coleoptera Associated with Decaying Wood in a Tropical Deciduous Forest - N Z Muñoz-López; A R Andrés-Hernández; H Carrillo-Ruiz; S P Rivas-Arancibia (Neotropical Entomology, 2016)

Influence of 5-chloro and 5-methyl benzotriazole on the corrosion of copper in acid solution: an experimental and a theoretical approach - A. Arancibia; J. Henriquez-Roman; M. A. Páez; L. Padilla-Campos; J. H. Zagal; J. Costamagna; G. Cárdenas-Jirón (Biotechnology Letters, 2005)

Gastric evacuation of the redspotted catshark under laboratory conditions - G. Aedo; H. Arancibia (Journal of Fish Biology, 2001)
An exponential model provided the best description of the gastric evacuation of the redspotted catshark Schroederichthys chilensis and predicted that 98% of a single initial meal was evacuated in 73·9 h at 16·3°C, slower than that reported for other elasmobranchs.